2019
DOI: 10.1136/bcr-2018-228237
|View full text |Cite
|
Sign up to set email alerts
|

Bacteraemia and multiple liver abscesses due toFusobacterium nucleatumin a patient with oropharyngeal malignancy

Abstract: Fusobacterium infections can have a wide clinical spectrum, ranging from mild infections to severe sepsis and abscess formation. This range depends partly on the patient’s underlying conditions, such as immunosuppression or malignancy. Fusobacteria are commensal rods in the oropharyngeal cavity and digestive tract, but should mucosal barrier disruption occur, in the presence of the above-mentioned predisposing conditions, fusobacteria can spread and cause infections in the soft tissues, liver and so on. An eld… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Several studies have identified increased abundances of the oral microbe Fusobacterium in setting of colorectal cancer ( 29 , 33 35 ), liver cirrhosis ( 36 38 ), primary sclerosing cholangitis ( 39 41 ), gastroesophageal reflux disease ( 42 46 ), HIV infection ( 47 49 ), alcoholism ( 50 ), and IBD ( 6 , 10 19 ). Given the prevalence of F. nucleatum in mucosal specimens, we tested the hypothesis that this pathobiont could promote an epithelial proinflammatory response and potentially contribute to intestinal inflammation.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have identified increased abundances of the oral microbe Fusobacterium in setting of colorectal cancer ( 29 , 33 35 ), liver cirrhosis ( 36 38 ), primary sclerosing cholangitis ( 39 41 ), gastroesophageal reflux disease ( 42 46 ), HIV infection ( 47 49 ), alcoholism ( 50 ), and IBD ( 6 , 10 19 ). Given the prevalence of F. nucleatum in mucosal specimens, we tested the hypothesis that this pathobiont could promote an epithelial proinflammatory response and potentially contribute to intestinal inflammation.…”
Section: Resultsmentioning
confidence: 99%
“… AF atrial fibrillation, HTN hypertension, CAD coronary artery disease, DM diabetes mellitus, NA not-applicable, S sensitive, N/T: Not-tested. Case 1, 3, 5, 7 [ 7 ], case 2 [ 20 ], case 4 [ 21 ], case 6 [ 22 ], case 8 [ 4 ], case 9 [ 23 ], case 10 [ 24 ], case 11 [ 25 ], case 12 [ 26 ], case 13 [ 5 ] …”
Section: Discussionmentioning
confidence: 99%